EXPERIMENTAL STUDY OF CARRYING CAPACITY GLULAM BEAMS, REINFORCED SPECIAL WAY - O. M. Ustarkhanov; M. H. Kalieva; R. I. Vishtalov; T. O. Ustarkhanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The paper deals a new structural solution of reinforced glued wooden beam and results ofexperimental studies of the bearing capacity of reinforced beams in a special way. We presentthedesign parameters ofprototypebeams, description ofthe experimental setup, results of experimental studies and comparative analysis ofthe stresses anddeflectionsdepending on how the pinching inclined armature.